Mycobacterium tuberculosis proteins involved in cell wall lipid biosynthesis improve BCG vaccine efficacy in a murine TB model. (March 2017) - Rao, Martin; Cadieux, Nathalie; Fitzpatrick, Megan; Reed, Steven; Arsenian, Sergei; Valentini, Davide; Parida, Shreemanta; Dodoo, Ernest; Zumla, Alimuddin; Maeurer, Markus
Abstract: Objectives: Advances in tuberculosis (TB) vaccine development are urgently required to enhance global disease management. We evaluated the potential of Mycobacterium tuberculosis ( M. tb )-derived protein antigens Rv0447c, Rv2957 and Rv2958c to boost BCG vaccine efficacy in the presence or absence of glucopyranosyl lipid adjuvant formulated in a stable emulsion (GLA-SE) adjuvant. Methods: Mice received the BCG vaccine, followed by Rv0447c, Rv2957 and Rv2958c protein boosting with or without GLA-SE adjuvant 3 and 6 weeks later. Immune responses were examined at given time points. 9 weeks post vaccination, mice were aerosol-challenged with M. tb, and sacrificed at 6 and 12 weeks to assess bacterial burden. Results: Vaccination of mice with BCG and M. tb proteins in the presence of GLA-SE adjuvant triggered strong IFN-γ and IL-2 production by splenocytes; more TNF-α was produced without GLA-SE addition. Antibody responses to all three antigens did not differ, with or without GLA-SE adjuvant. Protein boosting without GLA-SE adjuvant resulted in vaccinated animals having better control of pulmonary M. tb load at 6 and 12 weeks post aerosol infection, while animals receiving the protein boost with GLA-SE adjuvant exhibited more bacteria in the lungs. Conclusions: Our data provides evidence for developing Rv2958c, Rv2957 and Rv0447c in a heterologous prime-boost vaccination strategy with BCG.